DEVELOPMENT OF PROFESSIONAL COMPETENCE IN MILITARY PERSONNEL IN UZBEKISTAN - Shomuratov Zokhidjon Zokirovich; Dushanov Shokir Sharifovich; Ziyadullaev Abdukazar Shamsievich (Journal Park Publishing, 2024)
This article explores the development of professional competence among military personnel in Uzbekistan. The study investigates the various training programs, educational methodologies, and practical experiences that contribute to enhancing the skills, knowledge, and abilities of military personnel. It emphasizes the importance of a systematic approach to professional development, integrating theoretical knowledge with practical application, and highlights the role of continuous education and training in maintaining high standards of military readiness and effectiveness. The findings suggest that a well-structured professional development framework is crucial for the advancement of military competence, ensuring that personnel are equipped to meet the demands of modern military operations and national security challenges.
Keywords: Professional competence, Military personnel, Training programs, educational methodologies, Practical experiences, Continuous education, Military readiness, National security, Professional development framework.